2022
DOI: 10.1021/acs.est.1c07726
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Dependent Environmental Health Risk Analysis of Flupyradifurone

Abstract: Pesticides are used in agricultural production worldwide, resulting in widespread environmental pollution. Many diseases are closely related to exposure to pesticide residues. In this study, the association between exposure to the pesticide flupyradifurone (FPF), a substitute for neonicotinoids, and sexdependent thyroid dysfunction was explored for the first time. Exposure using rat models revealed that the FPF metabolism is sex-dependent, with males preferring N-dealkylation and hydrolytic metabolism and fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…The electrospray ion source temperature and spray voltage were set to 550 °C and 5500 V for the ESI+ and ESI− modes, respectively. 19 The lipids monitored by the pseudo-targeted lipidomics method were processed quantitatively (version 1.6, AB Sciex, Canada) using Analyst software.…”
Section: Lipidomic Analysismentioning
confidence: 99%
“…The electrospray ion source temperature and spray voltage were set to 550 °C and 5500 V for the ESI+ and ESI− modes, respectively. 19 The lipids monitored by the pseudo-targeted lipidomics method were processed quantitatively (version 1.6, AB Sciex, Canada) using Analyst software.…”
Section: Lipidomic Analysismentioning
confidence: 99%
“…Nontargeted metabolites in Lactiplantibacillus samples exposed to PAT were identified by using the method from Xu and Zhu et al [ 41 , 42 ]. Their research will be published in 2021 and 2022, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…12 Moreover, the broad-spectrum synergist piperonyl butoxide (PBO) is used in large quantities to treat crops and disinfest living facilities, consequently contaminating grain, with associated dietary risks. 13,14 Many studies have reported the molecular mechanisms underlying Neo-based toxicity in vertebrate models, such as oxidative stress, metabolism, 15 suspicious hepatocarcinogenicity, 16 thyroid homeostasis, 17 disorders of the reproductive axis, 18 and cholinergic transmission. 19 These toxic effects may occur during the process of breaking the parent compound down to produce metabolites.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Many studies have reported the molecular mechanisms underlying Neo-based toxicity in vertebrate models, such as oxidative stress, metabolism, suspicious hepatocarcinogenicity, thyroid homeostasis, disorders of the reproductive axis, and cholinergic transmission . These toxic effects may occur during the process of breaking the parent compound down to produce metabolites .…”
Section: Introductionmentioning
confidence: 99%